Porous membrane and method for producing water
By optimizing the crystal structure of poly1,1-difluoroethylene resin and the porous structure of the porous membrane, the occlusion problem of porous membrane when filtering easily contaminated filter stock solution is solved, and high pollution resistance and long-term high filtration flux are achieved.
Patent Information
- Application Number
- CN202380062540.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-07
- Filing Date
- 2023-09-25
- Publication Date
- 2025-04-11
AI Technical Summary
Existing porous membranes are prone to occlusion when filtering contaminated filter stock solution, resulting in a decrease in filtration flux. Washing with commonly used chemical reagents will damage the separation performance and mechanical strength of the membrane.
By controlling the crystal structure of poly1,1-difluoroethylene resin, the ratio of α-type structure crystallization to β-type structure crystallization is more than 0 and less than 0.50, and the pure water permeability and surface porous structure of the porous membrane are optimized to form a porous membrane with high pollution resistance and long-term high filtration flux.
It realizes efficient filtration of contaminated filter stock solution, reduces the adsorption of organic matter, extends the service life of porous membranes, and reduces the dependence on chemical reagents.
Smart Images

Figure CN119816358A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a porous membrane used in the fields of water treatment, pharmaceutical manufacturing, food industry, fermentation and the like. Background Art
[0002] In recent years, porous membranes such as microfiltration membranes and ultrafiltration membranes have been used in various fields such as water treatment fields such as water purification or drainage treatment, medical fields such as blood purification, and food industry fields. Recently, a porous membrane with high pollution tolerance is required that can efficiently filter the easily contaminated filter stock solution that has been considered difficult to filter so far. The so-called easily contaminated filter stock solution is characterized in that the filter stock solution contains more pollutants than usual, and the pollutants often contain organic matter. The so-called organic matter generally includes, for example, proteins, polysaccharides, humic acid, etc.
[0003] However, when the above-mentioned easily contaminated filtration stock solution is filtered, because the pollutants contained in a large number of filtration stock solutions and the porous membrane are blocked, the result is the problem that the filtration flux of the porous membrane is reduced. Particularly, in the case of a large number of organic easily contaminated filtration stock solutions, by the interaction of porous membrane and organic matter, the organic matter is adsorbed on the porous membrane etc. and becomes the starting point, and the hole of the porous membrane is easily blocked. Further, if the porous membrane is blocked and the number of holes tapers, high pressure is needed when filtering, and the pollutant components are pushed onto the porous membrane face under high pressure, so that adsorption is more likely to occur. In order to suppress the reduction of filtration flux, it is important to reduce the adsorption of organic matter to the porous membrane.
[0004] Here, as one of the methods to eliminate the adsorption of organic matter and restore the filtration flux, decomposing and removing the organic matter accumulated in the porous membrane using chemical reagents such as oxidants such as sodium hypochlorite and alkalis such as sodium hydroxide has been used as an effective means. However, since such chemical reagents not only decompose the accumulated organic matter but also decompose the polymers constituting the membrane, if the reagent washing is continuously performed, the membrane pores will be coarsened, and it is difficult to maintain the separation performance and mechanical strength of the membrane for a long time.
[0005] In contrast, Patent Documents 1 and 2 disclose methods for increasing the proportion of α-type structure crystals, which are stable crystals, in polyvinylidene fluoride resin (hereinafter also referred to as "PVDF resin"). It is disclosed that more stable crystals improve chemical resistance and enhance washing strength.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2015-73916
[0009] Patent Document 2: Japanese Patent Application Publication No. 2021-176629
[0010] Patent Document 3: Japanese Patent Application Publication No. 2017-29934 Summary of the invention
[0011] Problems to be solved by the invention
[0012] However, the α-type structural crystals in the porous membranes of polyvinylidene fluoride resins of Patent Documents 1 and 2 are TGTG' (T: trans, G: gauche) structures. Since the α-type structural crystals are torsion structures, the dipole moments are arranged in alternating directions and have no polarity. Therefore, the interaction with polar water molecules is weak, and on the contrary, the interaction with organic matter through hydrophobic interaction is strong. That is, the porous membrane formed by polyvinylidene fluoride resins with α-type structural crystals is prone to occlusion because organic matter is easily adsorbed. Therefore, it is necessary to wash with a large amount of chemical reagents. Although Patent Documents 1 and 2 improve the chemical resistance of the porous membrane, the chemical reagents are expensive and sometimes have adverse effects on the module components with the porous membrane and the process of separating the porous membrane. For example, the adhesive bonding the porous membrane deteriorates, and as a result, the life of the porous membrane assembly is sometimes shortened. When other separation membranes with lower chemical resistance are used in the later stage of the porous membrane, the separation membrane in the later stage is sometimes deteriorated.
[0013] Patent Documents 2 and 3 disclose porous membranes that contain not only α-type structural crystals but also β-type structural crystals as a relatively metastable phase. It is generally believed that β-type structural crystals are a TTTT planar sawtooth structure, with dipole moments arranged in the same direction, and have a large number of electron-donating components on the membrane surface, and have polarity. For example, Patent Document 2 discloses a membrane in which the proportion of infrared absorbance derived from α-type structural crystals and β-type structural crystals is 32.5%. That is, α-type structural crystals (H α ) and β-type structure crystal (H β ) ratio (H α / H β ) is 0.38. In addition, Patent Document 3 discloses a membrane in which the ratio of the α crystal structure to the β crystal structure is 0.11. Therefore, these membranes also have a strong interaction with polar water molecules, and on the contrary, organic matter is not easily adsorbed.
[0014] However, in the knowledge of the present inventors, the method for preparing the porous membrane of patent document 2 has a fast phase separation speed during membrane preparation, and it is easy to form a porous membrane with a large pore size. Due to the large pore size, the number of holes is insufficient. In such a porous membrane, pollutants easily invade the porous membrane and clog it, and the desired filtration amount cannot be obtained. Although it records that a variety of good solvents are mixed as solvents of polyvinylidene fluoride resin as a polymer in the membrane stock solution, it does not focus on the self-diffusion coefficient of the polymer, and the hydrogen bonding solvent described later is not included in the good solvent. In addition, in the method described in patent document 3, the self-diffusion coefficient of the polymer is also not focused on, and the content of the polymer in the membrane stock solution is as high as 30wt%, and the number of holes of the porous membrane to be made is small, and the pure water permeability is easy to become low. Such a porous membrane requires high pressure for filtration. Pollutants are pushed to the membrane surface under high pressure, which promotes adsorption and clogging of the porous membrane. Sufficient permeate cannot be obtained when filtering a filtration stock solution containing many pollutants.
[0015] The problem to be solved by the present invention is to obtain a porous membrane that can maintain high permeability of the filtrate even for the filtrate that is considered difficult to filter due to the significant contamination of the porous membrane, for the above-mentioned easily contaminated filtrate stock solution. In the prior art, as in Patent Document 1, a porous membrane containing a large number of α-type structural crystals is generally valued for chemical resistance. As mentioned above, in Patent Document 3, due to the high polymer concentration in the film-making stock solution, the phase separation rate tends to become slower, and it is easy to form a porous membrane containing a large number of β-type structural crystals as a metastable phase. On the other hand, the number of holes in the porous membrane is small, and the pure water permeability tends to become low. In addition, even as in Patent Document 2, when the polymer concentration in the film-making stock solution is low, a porous membrane containing a large number of β-type structural crystals is easily formed by using a mixed solvent. On the other hand, since the phase separation rate is not sufficiently slow, it is easy to form a porous membrane with a large pore size. That is, it is difficult to form a porous membrane having the following three elements: containing a large amount of β-structure crystals to be difficult to adsorb; increasing the number of surface pores to ensure flow paths and exhibit high pure water permeability; and having a small surface pore size.
[0016] The purpose of the present invention is to provide a porous membrane that can ensure a high filtration flux for a long time by further reducing the adsorption of easily contaminated filtration stock solution through high pure water permeability for a membrane with a large number of β-type structural crystals and excellent pollution resistance, and preventing pollutants from invading the porous membrane through a smaller surface pore size.
[0017] Means for solving problems
[0018] In order to solve the above-mentioned problems, the present invention provides a porous membrane having the following structure.
[0019] (1) A porous film comprising a polyvinylidene fluoride resin, wherein one surface is defined as a surface A and the other surface is defined as a surface B, and the α-type structure crystal (H) in the crystalline part of the polyvinylidene fluoride resin measured by the ATR method (attenuated total reflection method) on the surface A is α ) and β-type structure crystal (H β ) ratio (H α / H β The ratio of ) is 0 or more and 0.50 or less, and the pure water permeability of the porous membrane is 0.25m 3 / m 2 / h / 50kPa or above and 1.2m 3 / m 2 / h / 50 kPa or less, and an average value of the surface pore diameter of the surface pores in the surface A of the porous membrane is 5.0 nm or more and 12.0 nm or less.
[0020] (2) The porous film according to (1), wherein the crystallinity of the vinylidene fluoride resin in the surface A of the porous film is 30% or more.
[0021] (3) The porous membrane according to (1) or (2), wherein the removal rate of 40,000 Da dextran of the porous membrane is 45% to 80%.
[0022] (4) The porous membrane according to any one of (1) to (3), wherein the number of the surface pores [pores / μm 2 ] divided by the average value of the surface pore diameter [nm], the value X is 30 / μm 2 / nm or more and 100 / μm 2 / nm or less.
[0023] (5) The porous membrane according to any one of (1) to (4), wherein a standard deviation of the surface pore diameters in the surface A of the porous membrane is 1.0 nm or more and 5.0 nm or less.
[0024] (6) The porous film according to any one of (1) to (5), wherein a surface portion of the porous film from the surface A to a thickness of 10 μm is denser than an inner portion.
[0025] (7) A method for filtering a liquid, comprising using the porous membrane according to any one of (1) to (6).
[0026] (8) A membrane filtration device comprising the porous membrane according to any one of (1) to (6).
[0027] (9) A method for producing water, comprising a pretreatment step and a reverse osmosis membrane treatment step, wherein the pretreatment step pre-treats water to be treated to obtain water to be supplied to a reverse osmosis membrane, and the reverse osmosis membrane treatment step filters the water to be supplied to the reverse osmosis membrane through a reverse osmosis membrane to obtain permeate water, wherein the water to be treated has a biopolymer concentration of 100 μgC / L or more, and the water to be supplied to the reverse osmosis membrane whose biopolymer concentration is reduced to 75 μgC / L or less by the pretreatment is supplied to the reverse osmosis membrane,
[0028] The pretreatment step includes an ultrafiltration membrane treatment unit having an ultrafiltration membrane, and the ultrafiltration membrane is the porous membrane according to any one of (1) to (6).
[0029] (10) The method for producing fresh water according to (9), wherein the number of surface pores in the surface A of the porous membrane is 200 pores / μm. 2 Above and 2000 / μm 2 the following.
[0030] (11) The fresh water production method according to (9) or (10), characterized in that, in the ultrafiltration membrane treatment in the pretreatment step, the water to be treated does not contain a flocculant.
[0031] Effects of the Invention
[0032] According to the present invention, a porous membrane having a high ratio of β-type crystals to which organic matter is not easily attached, a small surface pore size, and a sufficiently large number of pores is obtained. Thus, a porous membrane having high water permeability and excellent pollution resistance and being able to ensure high permeability of filtrate for a long time even for easily polluted filtrate stock solution can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram showing the filtering condition of the porous membrane of the present invention.
[0034] Figure 2 This is a schematic diagram showing the filtration condition using a conventional porous membrane.
[0035] Figure 3 This is a schematic diagram showing the filtration condition using a conventional porous membrane.
[0036] Figure 4 Schematic diagram of the formation process of the porous membrane of the present invention.
[0037] Figure 5 This is an electron microscope photograph showing the surface (part) of the porous membrane according to one embodiment of the present invention.
[0038] Figure 6 This is a schematic diagram showing an example of the water generation method of the present invention. DETAILED DESCRIPTION
[0039] Hereinafter, the embodiments of the present invention will be described in detail with reference to the accompanying drawings, but the present invention is not limited thereto. In addition, in this specification, "mass" and "weight" have the same meaning. In addition, the so-called easily contaminated filtration stock solution is characterized in that the filtration stock solution contains more pollutants than usual, and the pollutants often contain useful substances that are the objects of removal. The so-called organic matter generally contains a large amount of, for example, proteins, polysaccharides, humic acid, etc.
[0040] The so-called contamination related to the "contamination resistance" of the present invention means that the porous membrane is blocked by organic matter contained in the filtration stock solution during the filtration process. If the clogging of the porous membrane by organic matter progresses, the filtration resistance increases and the amount of liquid that can pass through the porous membrane decreases.
[0041] Generally speaking, for porous membranes with α-type structural crystals, organic matter is easily adsorbed, and in order to eliminate the adsorption, the accumulated organic matter, etc., is decomposed and removed using a large amount of chemical reagents as an effective means. However, such chemical reagents not only decompose the accumulated organic matter, but also decompose the polymers constituting the membrane, and further sometimes have adverse effects on the modular components of the porous membrane and the process band separated from the porous membrane. Therefore, although there is hope for a porous membrane with β-type structural crystals with excellent pollution resistance, there is no porous membrane with β-type structural crystals and high water permeability. In the present invention, for a membrane with β-type structural crystals, it is further high in water permeability through pure water, thereby reducing adsorption of easily contaminated filtered stock solution, and can ensure high filtration flux. The following is an explanation of the porous membrane with improved pollution resistance of the present invention.
[0042] <About porous membrane>
[0043] The porous membrane according to an embodiment of the present invention is required to be a porous membrane containing a polyvinylidene fluoride resin, having a surface A and a surface B, wherein in the IR spectrum of the surface A measured by the ATR method (attenuated total reflection method), the α-type structure crystal (H) in the crystalline part of the polyvinylidene fluoride resin α ) and β-type structure crystal (H β ) ratio (H α / H β ratio) is greater than 0 and less than 0.5, and the pure water permeability is 0.25m 3 / m 2 / h / 50kPa or above and 1.2m 3 / m 2 / h / 50kPa or less. α / H β The ratio is 0, indicating β-type crystal structure (H β ) is 100%.
[0044] The α-type structure crystal (H α ) and β-type structure crystal (H β ) ratio (H α / H β ) needs to be greater than 0 and less than 0.50. Here, as the crystal structure of polyvinylidene fluoride resin, three structures are known, namely α-type, β-type, and γ-type which exist in very small amounts. Among them, generally speaking, attention is paid to α-type and β-type which are known to be formed in larger quantities compared to γ-type. It can be considered that the β-type structure crystallizes as a planar zigzag structure of TTTT, with the dipole moments arranged in the same direction, with many electron-donating components on the membrane surface, and has polarity. Therefore, the interaction with water molecules, which also have polarity, is strong, while organic matter is not easily adsorbed. Through H α / H β The ratio of H to α is 0 or more and 0.50 or less, thereby exhibiting excellent anti-fouling properties against organic substances. α ) and β-type structure crystal (H β ) ratio (H α / H β The ratio of H to H can be calculated by the following formula (1), and is more preferably 0.25 or more and 0.40 or less, and further preferably 0.30 or more and 0.40 or less. α / H β The smaller the ratio, the more β-type structure crystals there are, which is preferred.
[0045] The ratio of α-type / β-type structure crystals = H α / H β ...Formula (1).
[0046] The porous membrane of the present invention is characterized in that the β-type structure crystal (H β In the prior art, in order to obtain β-type structure crystals (H β), it is necessary to make the concentration of PVDF polymer high in the film-making process. If the polymer concentration of PVDF polymer is high, the density of the polymer of the generated porous film is improved, the voids are low and the number of holes decreases. Although there is an attempt to reduce the concentration of PVDF polymer in the film-making process to obtain β-type structure crystals, large holes are easily formed due to the low concentration, and a sparse porous film with a small number of holes is formed. In contrast, the porous film of the present invention controls the phase separation speed of the polymer and the solvent, so that even if the concentration of the PVDF polymer is low, a large number of fine holes can be generated. By becoming a slower phase separation speed during the phase separation process of the polymer and the solvent, the pore size can be made small and the number of holes can be generated in large quantities. As an indicator of the phase separation speed, the self-diffusion coefficient of the polymer can be used. By optimizing the concentration of the polymer, the solvent of the coagulation bath, and the temperature, a porous film with more β-type structure crystals, excellent pollution resistance, a small surface pore size, and a large number of holes can be obtained.
[0047] The main component of the porous membrane of the invention is a crystalline polymer resin containing polyvinylidene fluoride, and as long as the polymer resin constituting the porous membrane has crystals within 50 μm from the surface A of the porous membrane, its crystallinity is not limited, but the crystallinity of PVDF is more preferably 30% or more. By having a crystallinity of more than 30%, it is easy to suppress the deformation of the pores when the turbidity collides with the porous membrane, and the turbidity is easy to rebound from the membrane surface, which is preferred. In order to suppress the deformation of the pores and the rebound of the turbidity, the crystallinity is more preferably 35% or more, and further preferably 40% or more. However, if it is more than 80%, the softness of the porous membrane is lost, for example, it is easy to be damaged during operation using cross-flow operation, so it is preferably less than 80%. By H α / H β The ratio is small, and the crystallinity is more than 30%, so that the interaction with polar water molecules is strong, and the effect of organic matter not being easily adsorbed is easily obtained. When the crystallinity of the porous membrane is required, it can be calculated from the measurement results of a differential scanning calorimeter (hereinafter, DSC). The slices of the porous membrane within 50 μm from the outer surface used for the measurement of the crystallinity are taken and used with a commercially available freezing microtome. In the microtome, after the porous membrane is moved at a certain moving distance, the blade is brought into contact with the porous membrane and cut. The blade is set in a direction parallel to the surface of the porous membrane. First, the porous membrane is cut once by approaching the blade at a moving distance of 5 μm. Then, the moving distance is set to 40 μm, and it is further cut once, so that a thickness of 40 μm to 45 μm from the surface A can be taken.
[0048] The water permeability is 0.25m 3 / m 2 / h / 50kPa or above and 1.2m 3 / m2 / h / 50kPa or less, so that the easily contaminated filtration liquid can be filtered at a lower pressure. Since the pollutants are not pushed to the membrane surface under high pressure, the adsorption and occlusion of the porous membrane can be suppressed, and sufficient permeate can be obtained in the filtration of the filtration liquid with many pollutants. The pure water permeability is more preferably 0.30m 3 / m 2 / h / 50kPa or above and 1.2m 3 / m 2 / h / 50kPa or less, more preferably 0.40m 3 / m 2 / h / 50kPa or above and 1.2m 3 / m 2 / h / below 50kPa.
[0049] A schematic diagram showing the case where a filtration stock solution having high filtration difficulty is filtered using the porous membrane of the present invention is shown in FIG. Figure 1 middle. Figure 1 This is a conceptual diagram showing a portion of a cross section of a porous membrane. Figure 1 , the solid line depicted on the surface portion 102 schematically represents the mesh structure. The filtering direction FL is the direction from the surface portion 102 toward the interior 103. The organic matter in the filtered stock solution often contains coarse pollutants 201 and fine pollutants 202. The porous membrane is crystallized into a β-type structure, so that the polarity is high, which inhibits the adsorption of coarse pollutants 201 and fine pollutants 202. Furthermore, since pure water has high water permeability, the fine pollutants 202 can pass through the porous membrane at a relatively low pressure. At this time, since the fine pollutants 202 are not strongly pushed into the pores in the porous membrane, the adsorption and occlusion of the fine pollutants 202 on the porous membrane can be easily suppressed, and the high permeability of the filtrate can be maintained. In addition, the porous membrane 101 includes a surface portion 102 and an interior 103. The surface portion 102 is by a more dense structure compared with the inside 103, so that the polluting components are difficult to invade the porous film inside, so it is preferred to easily show excellent pollution resistance. If the micropores of the surface portion 102 are dense, then the coarse polluting components 201 can not invade in the porous film, and the surface layer 102 of the porous film are not blocked, and the porous film is difficult to pollute, which is preferred.
[0050] A schematic diagram showing the case where a difficult-to-filter stock solution is filtered using a porous membrane having large pores and having many α-type structure crystals known so far is shown in FIG. Figure 2The porous membrane has a low polarity due to the large number of α-type crystals, and the coarse pollutant components 201 and the fine pollutant components 202, which are organic substances, are easily adsorbed on the porous membrane through hydrophobic-hydrophobic interactions. In addition, due to the large pore size, the coarse pollutant components 201 invade the interior of the porous membrane and are easily blocked, and further, due to the small number of pores, the permeability of the filtrate is low.
[0051] Furthermore, a schematic diagram of filtering a difficult filtration stock solution using a porous membrane having a large number of β-type crystals and low pure water permeability is shown in FIG. Figure 3 Such porous membranes often have a small number of pores and low pure water permeability. Since the porous membrane has many β-type crystals, the adsorption of coarse pollutants 201 and fine pollutants 202 is less. However, since the pure water permeability is low, high pressure is required to allow the filtrate containing fine pollutants 202 to pass through the porous membrane. Therefore, the fine pollutants 202 are strongly pushed into the pores in the porous membrane, and adsorption to the porous membrane slowly occurs. Therefore, the permeability of the filtrate tends to become low.
[0052] The porous membrane of the present invention further has a dextran removal rate of 45% or more and 80% or less by weight average molecular weight 40,000Da, thereby preventing coarse pollutants and removal objects in the filtration stock solution from invading the membrane, and easily showing excellent pollution resistance. The dextran removal rate is more preferably 50% or more and 80% or less. The dextran removal rate can be calculated by the following formula (2) using a dextran aqueous solution prepared by filtering the porous membrane at a cross-streamline velocity of 1.0m / sec and a membrane pressure difference of 10kPa using a commercially available dextran with a weight average molecular weight of 40,000Da at 1000ppm and 25°C.
[0053] T = {(refractive index of original solution) - (refractive index of transmitted solution)} / (refractive index of original solution) × 100 ... Formula (2)
[0054] Here, the cross-stream velocity is the value obtained by dividing the flow rate in the direction perpendicular to the filtration direction of the filtrate by the cross-sectional area of the flow path of the flow. In addition, the so-called transmembrane pressure difference is the difference between the pressure on the filtrate side and the pressure on the permeate side across the porous membrane.
[0055] The average value of the surface pore size [nm] of the surface portion of the porous membrane is 5.0 nm or more and 12 nm or less, thereby preventing the coarse contamination components in the filtered stock solution and the removal object from invading the porous membrane, and easily showing high pollution resistance, which is preferred. The average value of the surface pore size [nm] of the surface portion is further preferably 5.0 nm or more and 8.0 nm or less. The so-called surface pore size is the diameter of the pores present in the surface when the surface of the porous membrane is observed. In the case of finding the surface pore size of the porous membrane, the image obtained by the SEM observed on the surface of the porous membrane is binarized using the free software "ImageJ". When binarization is performed, after CreateBackground is performed using Subtract Background as 1 pixel, the condition is selected in Threshold (binarization threshold): RenyiEntropy. In the resulting binary image, select Area in Analyze Particles to find the area of each hole, and the diameter calculated by assuming each hole to be a circle is used as the surface pore size. When the average value of the surface pore diameter is obtained, the pore diameters of one thousand or more pores are averaged and obtained.
[0056] The standard deviation of the surface pore size [nm] of the porous membrane is more than 1.0nm and less than 5.0nm, so that the load of the pollutant to the porous membrane can be uniform, and it is easy to show excellent pollution resistance, which is preferred. The standard deviation is more than 1.0nm and less than 5.0nm, so that the load of the pollutant to the porous membrane can be uniform, and it is easy to show excellent pollution resistance, which is preferred. The standard deviation of the surface pore size is more preferably more than 1.0nm and less than 4.0nm, and more preferably more than 1.0nm and less than 3.0nm. The standard deviation of the surface pore size can be obtained by analyzing the SEM image observed on the surface of the porous membrane as described above.
[0057] The number of surface pores observed on the surface of the porous membrane is 200 / μm. 2 ~2000 / μm 2 , so that the pollutants in the filtration stock solution can be dispersed in the porous membrane, and it is easy to implement the filtration of highly turbid water stably for a long time, which is preferred. Even if the pollutants in the filtration stock solution block some of the surface pores as the filtration progresses, if the number of surface pores is large, it is easy to fully ensure the number of flow paths for the filtration stock solution to pass through the porous membrane, which is preferred. If the number of surface pores is 200 / μm 2 The above values make it easy to ensure a sufficient flow path until back pressure washing or other washing is performed even for a filtrate raw liquid that is easily contaminated. The number of pores on the surface of the porous membrane is more preferably 290 pores / μm. 2 ~1500 / μm 2, particularly preferably 350 / μm 2 ~1000 / μm 2 . The so-called number of surface pores of a porous membrane is the number of pores present in the surface when the surface of the porous membrane is observed. In order to determine the number of surface pores of a porous membrane, the image obtained by SEM that observed the surface of the porous membrane was binarized using the free software "ImageJ". When binarization was performed, after Create Background using Subtract Background as 1 pixel, the condition "RenyiEntropy" was selected in Threshold (binarization threshold). In the resulting binary image, the number of pores in the range observed by Analyze Particles was determined. When determining the number of surface pores per unit area [pores / μm 2 ] In the case of more than one thousand holes, the value is calculated by dividing the total area of the region where the number of holes was observed.
[0058] The value X obtained by dividing the number of surface pores by the average surface pore diameter is 30 pores / μm. 2 / nm or more and 100 / μm 2 / nm or less, so as to prevent the contaminants in the filtration stock solution from invading the pores, and to ensure that the number of permeate flow paths through the porous membrane is sufficient, so that the permeate is easy to show, which is preferred. X is more preferably 50 pieces / μm 2 / nm or more and 100 / μm 2 / nm or less, more preferably 60 / μm 2 / nm or more and 100 / μm 2 / nm or less. The number of surface pores of the porous membrane can be obtained by binarizing the image obtained by SEM observed on the surface of the porous membrane and analyzing it by Analyze Particles in the same way as the case of obtaining the surface pore size. The number of pores per unit area is obtained by dividing the number of surface pores by the area of the analyzed image. The image containing more than 1000 pores is analyzed and calculated in the same way as the pore size.
[0059] In addition, the porous membrane in the present application preferably has a nano-network structure on its surface. The so-called nano-network structure means that in the surface of the porous membrane, in the outermost portion from the surface to a thickness of 2 μm, the average cross-sectional pore diameter [nm] in the cross section of the outermost portion is 1nm to 99nm, and the number of cross-sectional pores is 100 / μm. 2 ~1000 / μm 2. The porous membrane is preferably characterized by having a nano-network structure, which makes it easy for the porous membrane to show excellent pollution resistance. In addition, the so-called cross-sectional pores refer to the pores observed in the cross section of the outermost surface. Since the average value of the cross-sectional pore size [nm] in the cross section of the outermost surface is 1nm to 99nm, which is fine, it is easy to prevent the coarse pollutants in the filtration stock solution from being captured on the outermost surface of the porous membrane and the removal object from invading the porous membrane. Furthermore, since the number of cross-sectional pores is as high as 100 / μm 2 ~1000 / μm 2 Therefore, the holes are formed in all directions, and the flow paths are easily connected in a straight line, and it is difficult to block when the fine pollutant components pass through the porous membrane. In addition, even if some of the holes are blocked, the flow path of the filtered stock solution through the porous membrane can be ensured, so the porous membrane is easy to show excellent pollution resistance, which is preferred.
[0060] <About the method for producing porous film>
[0061] The porous membrane of the present invention can be obtained by the following manufacturing method, which comprises a step (A): a step of dissolving a polymer in a solvent to obtain a polymer solution, and a subsequent step (B): a porous membrane forming step of solidifying the polymer solution in a non-solvent to form a porous membrane, wherein the self-diffusion coefficient [m 2 / sec] is 0.8 × 10 -11 m 2 / second~1.6×10 - 11 m 2 / sec, the non-solvent used in step (B) contains 90 to 100 wt % of water, and the temperature of the non-solvent is 6°C to 45°C.
[0062] The type of polymer used in step (A) is not particularly limited. Specific examples thereof include polysulfone resins, polyethersulfone resins, polyvinylidene fluoride resins, nylon, cellulose esters such as cellulose acetate and cellulose acetate propionate, fatty acid vinyl esters, polyvinyl alcohol, polyvinyl acetate, polyvinyl pyrrolidone, polymers of acrylic acid esters or methacrylic acid esters such as ethylene oxide, propylene oxide, or polymethyl methacrylate, and copolymers thereof.
[0063] In particular, in order to use the porous membrane for long-term filtration, it is preferred that the accumulated pollutants are regularly washed with reagents, and it is preferred to contain a polyvinylidene fluoride resin that is particularly excellent in chemical resistance. The so-called polyvinylidene fluoride resin refers to a homopolymer of 1,1-difluoride or a copolymer of 1,1-difluoride. The so-called copolymer of 1,1-difluoride here refers to a polymer having a 1,1-difluoride residue structure. The polymer having a 1,1-difluoride residue structure is typically a copolymer of a 1,1-difluoride monomer and a fluorine-based monomer other than it. As such a fluorine-based monomer, for example, vinyl fluoride, tetrafluoroethylene, hexafluoropropylene or chlorotrifluoroethylene can be cited. In the above-mentioned copolymer of 1,1-difluoride, ethylene other than the above-mentioned fluorine-based monomer can be copolymerized to the extent that the effect of the present invention is not impaired.
[0064] When the weight of the porous membrane is set to 100%, the polyvinylidene fluoride resin preferably contains 50% by weight or more, and particularly preferably contains 60% by weight or more. The weight average molecular weight of the polymer is 5 to 1,000,000 Da, so that the self-diffusion coefficient described later can be easily controlled within a slower and suitable range, which is preferred. In addition, multiple polymers can be used in combination.
[0065] The solvent preferably contains a good solvent. Here, the term "good solvent" refers to a solvent that can dissolve more than 5% by weight of the polymer in a low temperature region below 60°C. As a good solvent, for example, N-methyl-2-pyrrolidone (hereinafter, "NMP"), 2-pyrrolidone (hereinafter, "2P"), ε-caprolactam (hereinafter, "ε-CL"), dimethyl sulfoxide (hereinafter, "DMSO"), dimethylacetamide (hereinafter, "DMAc"), dimethylformamide (hereinafter, "DMF"), methyl ethyl ketone, acetone, tetrahydrofuran, tetramethyl urea or trimethyl phosphate or a mixed solvent thereof. The good solvent is further preferably contained in the solvent in an amount of 40% by weight or more, and particularly preferably contained in an amount of 60% by weight or more. By containing a large amount of a good solvent, the polymer chain is extended in the polymer solution, and it is easy to control the self-diffusion coefficient described later in a slower and suitable range, so it is preferred.
[0066] Here, the so-called "non-solvent" in step (B) refers to a solvent that does not dissolve or swell the polymer even if the non-solvent is heated to a high temperature or even at a boiling point. Examples of the non-solvent include water, hexane, pentane, benzene, toluene, methanol, ethanol, carbon tetrachloride, o-dichlorobenzene, trichloroethylene, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, or aliphatic hydrocarbons such as low molecular weight polyethylene glycol, aromatic hydrocarbons, aliphatic polyols, aromatic polyols, chlorinated hydrocarbons, or other chlorinated organic liquids or mixed solvents thereof. In order to control the self-diffusion coefficient to a suitable range, the concentration (weight %) of the polymer in the polymer solution is preferably above the entanglement concentration, more specifically, preferably 10 to 40 weight %, further preferably 12 to 30 weight %, and particularly preferably 15 to 25 weight %.
[0067] The porous film forming step of solidifying the polymer solution in step (B) in a non-solvent to form a porous film is a so-called porous film forming step using non-solvent-induced phase separation. If the polymer solution contacts the non-solvent, the polymer cannot be completely dissolved in the solvent, and the phase is separated into a phase containing a large amount of the polymer and a phase containing a large amount of the solvent, and each phase is coarsened while agglomerating with the same phase around it.
[0068] Figure 4 The process of forming the porous membrane in step (B) is schematically shown. Figure 4 In the order of (a) to (f), phase separation is performed in the polymer solution, and the location with high polymer concentration (phase 301 containing a large amount of polymer) is coarsened. During the phase separation and / or coarsening process, the solvent and the non-solvent are exchanged. If the concentration of the non-solvent increases to a certain level, the polymer solidifies and the structure of the porous membrane is fixed. At this time, the phase 302 containing a large amount of solvent becomes the pores of the porous membrane.
[0069] The inventors have conducted intensive research and found that, in the manufacture of the porous membrane of the present invention, the self-diffusion coefficient of the polymer is set to a relatively low range of 0.8×10 -11 m 2 / second~1.6×10 -11 m 2 / sec, thereby suppressing the progress of phase separation and coarsening, and the phase 301 containing a large amount of polymers and the phase 302 containing a large amount of solvents can be solidified in a fine and large amount state. -11 m 2 / sec or more, thus having a sufficient diffusion coefficient for phase separation between the polymer and the solvent, and pores are easily formed. When the diffusion of the polymer is too slow to be easily separated, pores are difficult to form. -11 m 2 / sec or less, thereby easily suppressing the excessive phase separation and coarsening progress, suppressing the coalescence of pores and forming a large number of micropores. That is, by appropriately controlling the self-diffusion coefficient of the polymer in a relatively low range, a porous membrane with a large number of micropores can be formed. The self-diffusion coefficient is more preferably 0.8×10 -11 m 2 / second~1.4×10 -11 m 2 / second, more preferably 0.8×10 -11 m 2 / second~1.1×10 -11 m 2 / Second.
[0070] The self-diffusion coefficient can be determined by all-atom molecular dynamics calculation. All-atom molecular dynamics calculation is a method of solving the motion equation of the molecular group system for all constituent atoms one by one to obtain the trajectory of each atom. First, a polymer solution system is prepared in a manner that becomes the actual polymer concentration (weight %). At this time, a model polymer chain is modeled in a manner that has a molecular weight of 800 to 6000 and is 1 / 200 to 1 / 5 of the weight average molecular weight of the polymer actually used. Among the potential parameters used in molecular dynamics calculations, known parameters such as DREIDING [SL Mayo, BD Olafson, WA Goddard III, J. Phys. Chem. 94, 8897 (1990)], GAFF [J. Wang, RM Wolf, JW Caldwell, PA Kollman, DACase, J. Comput. Chem. 25, 1157 (2004)], OPLS-AA [WL Jorgensen, DS Maxwell, Julian Tirado-Rives, J. Am. Chem. Soc. 118, 11225 (1996)], and CHARMM [BR Brooks, RE Bruccoleri, BD Olafson, DJ States, S. Swaminathan, M. Karplus, J. Comput. Chem. 4, 187 (1983)] can be used, but it is preferred to use parameters that reproduce the density and cohesive energy, which are physical quantities representing the flocculation state of a solution system.
[0071] The inventors studied the reproducibility of the flocculation state, and found that GAFF or OPLS-AA is particularly preferred. In addition, the temperature is controlled to 25°C by the Nose-Hoover method [Hoover, WG Phys. Rev. A, 31, 1695 (1985).], and the pressure is controlled to 1 bar by the Andersen method [HC Andersen, J. Chem. Phys. 72, 2384 (1980)], thereby forming a pressure / temperature constant ensemble. At this time, the short-range Lennard-Johns interaction is operated by applying a switching function from 1.0nm and cutting off at 1.2nm, and the long-range electrostatic interaction is calculated by the Particle Mesh Ewald method. In the pressure / temperature constant ensemble, after the molecular dynamics calculation is performed until the density becomes constant, the unit cell length is adjusted in a manner to achieve an average density, and an additional calculation of 11ns is performed in the temperature constant ensemble. Using a 10 ns trajectory, the mean square displacement (MSD) of each atom of the polymer is obtained, and the self-diffusion coefficient of the polymer is calculated by the following formula (3). At this time, regarding the range of MSD and t used in the calculation of D, it is confirmed that the value obtained by dividing log (MSD) by log (t) is in the range of 0.9 to 1.1. In the case of mixing multiple polymers to prepare a polymer solution, the value obtained by weighted averaging the self-diffusion coefficients of each polymer based on the weight % of the polymer is used as the self-diffusion coefficient of the polymer in the polymer solution.
[0072] D=MSD / 6t...Equation (3)
[0073] D: self-diffusion coefficient t: time
[0074] In the manufacture of the porous membrane of the present invention, the non-solvent used for coagulation contains 90 to 100% by weight of water, so that the coagulation is fast, and the self-diffusion coefficient in the polymer solution is easy to affect the speed of phase separation and coarsening. In addition, the temperature of the non-solvent is 6°C to 45°C, so that the coagulation is fast, and the self-diffusion coefficient in the polymer solution is easy to affect the speed of phase separation and coarsening. The temperature of the non-solvent is preferably 35°C to 40°C. By making the temperature of the non-solvent 35°C to 40°C, the coagulation is particularly fast, and the crystal form can generate a large amount of β-type structure crystals. That is, as described above, by suppressing the self-diffusion coefficient of the polymer in the polymer solution to a low range, and at the same time, the solvent in the polymer solution is efficiently exchanged with the non-solvent in the coagulation bath, the coagulation is further accelerated, so that a porous membrane with a large number of surface pores and a high proportion of β-type structure crystals can be obtained.
[0075] Regarding the manufacture of the porous membrane of the present invention, in the above-mentioned step (A), the above-mentioned solvent contains a hydrogen-bonding solvent with a molecular weight of less than 500Da having hydrogen-bonding donor and hydrogen-bonding acceptor properties, which is easy to control the self-diffusion coefficient of the polymer within an appropriate range, and is preferred. The so-called hydrogen-bonding donor refers to a positively polarized hydrogen atom, specifically, a hydroxyl group (OH group), a carboxyl group (COOH group), an amino group (NH group), etc. The so-called hydrogen-bonding acceptor refers to a lone electron pair, specifically, a carbonyl group, an alkoxy group, a cyano group, etc. The solvent is a hydrogen-bonding donor and a hydrogen-bonding acceptor, so that the interaction brought about by the hydrogen bond between the solvent and the solvent is strong, the movement of the solvated polymer is suppressed, and the self-diffusion coefficient of the polymer is easily controlled within a slower and suitable range. The solvents with hydrogen-bonding donor and hydrogen-bonding acceptor properties are not particularly limited, and specific examples include 2P, ε-CL, 1,3-dimethylurea, N-methylacetamide, hydantoin, 2-imidazolidinone, DL-pyroglutamic acid, etc.
[0076] In the above-mentioned step (A), it is preferred that the self-diffusion coefficient of the polymer is easily controlled within an appropriate range by including the polymer having hydrogen bond donor and / or hydrogen bond acceptor properties by the dissolved polymer. The reason is that the polymer is hydrogen bond donor and / or hydrogen bond acceptor properties, so that the self-diffusion coefficient of the polymer is easily controlled within a slower and suitable range by interacting with the solvent having hydrogen bond donor and hydrogen bond acceptor properties through hydrogen bonds. From the viewpoint of controlling the self-diffusion coefficient of the polymer within an appropriate range, it is more preferred that the polymer having hydrogen bond donor and / or hydrogen bond acceptor properties comprises 10 wt % to 50 wt % in the porous membrane.
[0077] Furthermore, the value obtained by dividing the number of moles of hydrogen bond acceptor functional groups contained in the solvent of the above step (A) by the number of moles of hydrogen bond donor functional groups contained in the polymer having hydrogen bond donor properties and / or hydrogen bond acceptor properties is 1.0 to 12, so that the hydrogen bond between the polymer and the solvent is in an appropriate range, and the self-diffusion coefficient of the polymer is easily controlled in a relatively slow and appropriate range. This value is more preferably 2.0 to 9.0, and particularly preferably 5.4 to 8.0.
[0078] The value obtained by dividing the number of moles of hydrogen bond donor functional groups contained in the solvent of the above step (A) by the number of moles of hydrogen bond acceptor functional groups contained in the polymer having hydrogen bond donor and / or hydrogen bond acceptor properties is 0.5 to 5.0, so that the hydrogen bond between the polymer and the solvent is in an appropriate range, and the self-diffusion coefficient of the polymer is easily controlled in a relatively slow and suitable range. This value is more preferably 1.5 to 2.3, and particularly preferably 1.8 to 2.3.
[0079] The porous membrane of the present invention may further have other layers. In this case, it is preferred that the porous membrane of the present invention is configured on the surface portion. By configuring the porous membrane of the present invention on the surface portion, the components contained in the filtered stock solution are not easy to invade the inside of the porous membrane, and high permeability can be maintained for a long time. As long as the above-mentioned other layers are constituent elements that can overlap with the porous membrane to form a layered state, there is no particular limitation, and it is preferred that the above-mentioned other layers are supports. Here, the so-called "support" refers to a structure that is used to physically enhance the porous membrane and has a higher breaking strength than the porous membrane. In order to improve the breaking strength of the support, the breaking strength (breaking strength per unit area) of the support is preferably more than 3MPa, more preferably more than 10MPa. In addition, when the other layers and the porous membrane of the present invention are configured as a layered composite membrane that is hollow filamentous, the breaking strength of the support is preferably more than 300gf, more preferably more than 800gf.
[0080] Liquid filtration can be performed by using a membrane filtration device using a porous membrane of the present invention obtained by the above-mentioned operation. As a membrane filtration device, for example, a device having a raw water tank, a booster pump, a module composed of thousands to tens of thousands of porous hollow fiber membranes of the present invention, a filtered water tank, a backwash pump, etc. can be considered, but it is not limited to these. As a method for filtering liquid, for example, the raw liquid such as factory drainage can be operated using the above-mentioned membrane filtration device at an operating pressure of 10kPa to 1MPa to remove organic matter contained in the raw water, but it is not limited to these.
[0081] Fresh water systems using reverse osmosis membranes are used in desalination of seawater, a wide range of industries, and water treatment fields, and have proven superior to other separation methods in terms of separation performance, energy efficiency, etc. On the other hand, the fresh water systems have the problem of rapid increase in membrane pressure difference and reduction in membrane permeability and separation performance due to microbial proliferation on the membrane surface or biofilm adhesion to the membrane surface, i.e., biofouling.
[0082] When the membrane pressure difference increases or the membrane permeability and separation properties decrease due to biological fouling, the membrane is generally washed. As a washing method, there are: temporarily stopping filtration and supplying raw water and filtered water to the membrane surface for washing, so-called flushing washing; reagent washing using detergents for washing. However, once the fouling progresses, even if washing is performed, the membrane pressure difference, permeability, and separation properties cannot be fully restored, and the frequency of washing gradually increases, and eventually the membrane cannot be operated, and the membrane needs to be replaced.
[0083] Japanese Patent No. 6561082 and Japanese Patent No. 6630689 disclose a method for membrane separation by focusing on biopolymers contained as part of organic matter in treated water, adjusting the biopolymers in treated water to be below a predetermined threshold value, the predetermined threshold value being any value in the range of 9 μg / L to 12 μg / L or 9 μg / L to 17 μg / L. Biopolymers are hydrophilic macromolecular organic substances (polysaccharides, proteins, etc.) having a molecular weight of about 10 to 20 kDa or more in organic matter.
[0084] However, the inventors measured the biopolymer concentration of seawater during the research of the present invention and found that it was 122 to 218 μgC / L, which is a very low concentration compared to the prescribed threshold values disclosed in Japanese Patent No. 6561082 and Japanese Patent No. 6630689. For treated water such as general seawater and sewage treatment water, the biopolymer concentration is high as described above, and it is difficult to achieve the prescribed threshold values disclosed in Japanese Patent No. 6561082 and Japanese Patent No. 6630689. In addition, as the supply object, it is assumed that it is not a reverse osmosis membrane but a microfiltration membrane or an ultrafiltration membrane, which has a different contamination mechanism from the reverse osmosis membrane and is therefore difficult to apply directly.
[0085] Therefore, the present invention suppresses the progress of contamination of the pretreatment process and the reverse osmosis membrane for treated water with high biological contamination potential, such as when desalting seawater, brackish water, etc. by using a membrane to obtain fresh water, purifying sewage treatment water, industrial wastewater, etc. to obtain reused water, etc. In order to solve the above-mentioned problems, the water production method in the present invention includes any one of the following structures. A water production method, including a pretreatment process and a reverse osmosis membrane treatment process, the pretreatment process pre-treats the treated water to obtain water for supplying to the reverse osmosis membrane, the reverse osmosis membrane treatment process filters the water for supplying to the reverse osmosis membrane with a reverse osmosis membrane to obtain permeated water, in the water production method, the treated water with a biopolymer concentration of more than 100μgC / L is pre-treated to make the biopolymer concentration less than 75μgC / L, and the obtained water for supplying to the reverse osmosis membrane is supplied to the reverse osmosis membrane, the pretreatment process has an ultrafiltration membrane treatment, and the ultrafiltration membrane is the porous membrane described above.
[0086] The water production method of the present invention is implemented in a water production system in which the water to be treated 401 is pretreated through an ultrafiltration membrane and then treated through a reverse osmosis membrane 402 to be separated into permeate water 403 and concentrated water 404. Examples of the water to be treated include seawater, brackish water, river water, lake and marsh water, groundwater, sewage, and secondary treated sewage water. Since the water to be treated contains solid components such as turbidity, if it is directly filtered through the reverse osmosis membrane, the solid components adhering to the membrane surface will increase, the pressure difference will rise sharply, and it cannot operate. Therefore, the water to be treated 401 is pre-treated through a pretreatment process 405 to produce water 406 for supplying to the reverse osmosis membrane and then supplied to the reverse osmosis membrane.
[0087] In the present invention, in order to suppress the progress of fouling of the reverse osmosis membrane, the water to be treated 1 with a biopolymer concentration of 100 μgC / L or more is pretreated to make the biopolymer concentration 75 μgC / L or less, and the resulting water 406 for supplying to the reverse osmosis membrane is supplied to the reverse osmosis membrane as a feature. It is further preferred that the water to be treated 401 with a biopolymer concentration of 100 μgC / L or more is pretreated to make the biopolymer concentration 50 μgC / L or less, and the water 406 for supplying to the reverse osmosis membrane is supplied to the reverse osmosis membrane. On the other hand, in order to pretreat the water to be treated 401 with a biopolymer concentration of 100 μgC / L or more to make the biopolymer concentration less than 20 μgC / L, a large amount of energy and cost are required. It is preferred to make the biopolymer concentration 20 μgC / L or more and supply the water 406 for supplying to the reverse osmosis membrane to the reverse osmosis membrane.
[0088] Biopolymers are hydrophilic high molecular organic substances (polysaccharides, proteins, etc.) with a molecular weight of about 10 to 20 kDa or more in organic matter. As for the definition and determination method of biopolymers, for example, as described in Huber, SA, Balz, A., Abert, M., Pronk, W., 2011. Characterization of aquatic humic and non-humic matter with size-exclusion chromatography e organic carbon detection e organic carbon detection e organic nitrogen detection (LC-OCD-OND). Water Research 45 (2), 879-885, it can be determined by organic carbon detection type exclusion chromatography (LC-OCD). Here, the so-called LC-OCD method is an analytical method that fractionates the TOC components in the sample according to molecular weight and displays it as a chromatogram. On the chromatogram, there is a tendency that the retention time of organic matter with larger molecular weight and hydrophilicity is shorter. As the measuring conditions of the LC-OCD method, the following conditions can be adopted: using 250mm×20mmTSK HW50S as a column, making the flow rate 1.1mL / min, making the sample injection amount 1mL, making the UV wavelength 254nm, making the acid injection amount to the OCD meter 0.2mL / min, using pH6.85 phosphate buffer as an eluent, and using a solution of 4mL O-phosphoric acid (85%) and 0.5g of potassium persulfate added to 1L of ultrapure water as an acidifying solution. As the measuring device used in the LC-OCD method, for example, a LC-OCD device (manufactured by DOC-Labar) in which a wet total organic carbon meter (OCD meter) is connected to a high performance liquid chromatography (HPLC) can be used.
[0089] The porous membrane of the present invention can be used as an ultrafiltration membrane. That is, the water production method of the present invention can use the following porous membrane as an ultrafiltration membrane, wherein the porous membrane is a porous membrane containing polyvinylidene fluoride resin, has a surface A and a surface B, and in the ATR method (attenuated total reflection method) of the surface A, the α-type structure crystal (H α ) and β-type structure crystal (H β ) ratio (H α / H β ) is greater than 0 and less than 0.50, and the pure water permeability is 0.25m 3 / m 2 / h / 50kPa or above and 1.2m 3 / m 2 / h / 50 kPa or less, and an average value of the surface pore diameter in the surface A of the porous membrane is 5.0 nm or more and 12.0 nm or less.
[0090] As an ultrafiltration membrane, a porous membrane with a removal rate of 40,000 Da dextran of 45% or more and 80% or less is preferred. By having a dextran removal rate of 45% or more and 80% or less, coarse pollutants and removal objects in the filtration stock solution are prevented from invading the membrane, and excellent pollution resistance is easily displayed. In addition, the biopolymer removal rate of the membrane is easy to increase, so that the amount of flocculant added can be reduced or not used at all, and the biopolymer concentration of water provided to the reverse osmosis membrane can be 75μgC / L or less. The so-called treated water does not contain a flocculant, which means that no flocculant is added to the treated water, that is, no flocculant is used in the treated water. As long as the flocculant flocculates the biopolymer, the type of compound is not limited, which is equivalent to a concentration of 0% to 0.05% of the flocculant. In particular, the ultrafiltration membrane has a dextran removal rate of 45% or more and 80% or less with a weight average molecular weight of 40,000 Da, and more preferably 50% or more and 80% or less.
[0091] As long as the salt concentration of the reverse osmosis membrane 2 can be reduced in a manner that the treated water can be used for drinking water, industrial water, urban water, etc., any raw material membrane can be used, and for example, a membrane composed of raw materials of cellulose acetate and polyamide can be cited. Among them, a membrane composed of raw materials of polyamide is particularly effective in the method of the present invention. Since the polyamide membrane has low resistance to chlorine, which is most commonly used as a bactericide to prevent the proliferation of biofilm, even a slight concentration of chlorine significantly deteriorates the membrane, making it difficult to prevent biological contamination. Therefore, the effect brought about by the implementation of the present invention is significantly manifested.
[0092] The lower the water permeability reduction rate of the reverse osmosis membrane, the longer the interval between reagent washing of the reverse osmosis membrane and the less frequent the exchange. In addition, when the reverse osmosis membrane is operated at a low flow rate, the increase in the operating pressure difference can be suppressed. As a result, the number of reverse osmosis membranes required for water production is reduced, which is preferred. The water permeability reduction rate of the reverse osmosis membrane is preferably 0.20 (% / hr) or less, and more preferably 0.18 (% / hr) or less.
[0093] Example
[0094] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited to these Examples. First, the measurement method and the evaluation method are shown below.
[0095] (i) Measurement of the ratio of α-type structure crystals to β-type structure crystals in the crystal part of PVDF resin
[0096] The IRTracer-100 produced by Shimadzu Corporation was used to analyze the -1 The IR spectrum of the film surface was measured. Based on the measured area, the IR spectrum at 763 cm -1 The peak height of the signal of the α-type structure crystal at the position where α ), and at 840cm -1 The peak height of the signal of the β-type structure crystal (H β ), and the ratio of α-type structure crystals to β-type structure crystals was calculated using the following formula.
[0097] The ratio of α-type / β-type structure crystals = H α / H β ...Formula (1).
[0098] (ii) Pure water permeability
[0099] A small module with a length of about 10 cm and composed of about 1 to 10 hollow fiber membranes was prepared. Distilled water was fed from surface A to filter the entire volume under the conditions of a temperature of 25°C and a filtration pressure difference of 18.6 kPa. The permeate volume (m 3 ), and convert the obtained value into unit time (hr), unit effective membrane area (m 2 ), calculated for every 50kPa.
[0100] (iii) Evaluation method for removal rate of dextran with a weight average molecular weight of 40,000 Da
[0101] Dextran (manufactured by Aldrich; weight average molecular weight 40,000 Da) was mixed with 1000 ppm distilled water to prepare a dextran aqueous solution. The prepared dextran aqueous solution was supplied to a porous membrane at 25°C in such a manner that the membrane pressure difference was 10 kPa, and cross-flow filtration was performed at a cross-flow velocity of 1.0 m / s, and the permeate was sampled. The dextran aqueous solution (stock solution) supplied to the porous membrane was sampled at the same time as the permeate was sampled. The refractive index of the permeate and the stock solution was measured, and the removal rate was calculated based on formula (2): T.
[0102] T = {(refractive index of original solution) - (refractive index of transmitted solution)} / (refractive index of original solution) x 100 ... formula (2).
[0103] (iv) Measurement of crystallinity of polymer resin constituting porous membrane
[0104] Determination of the crystallinity of the polymer resin of the porous membrane showing the shape of the hollow fiber membrane. The measurement used a slice within 50 μm from the outer surface of the hollow fiber membrane. The outer surface of the hollow fiber membrane was cut using a commercially available cryostat (manufactured by Leica; Jung CM3000) to collect the sample. The hollow fiber membrane immersed in distilled water was frozen at -20°C using a cryostat (manufactured by Leica; Jung CM3000), and a blade was set in a direction parallel to the surface of the hollow fiber membrane. First, the hollow fiber membrane was cut once by moving the blade close to the blade at intervals of 5 μm. Then, the moving distance was set to 40 μm, and it was further cut once, so that a hollow fiber membrane slice with a thickness of 40 to 45 μm from the surface was collected. When the slice is placed in DSC (DSC6200 manufactured by SEIKO) and the temperature is raised from room temperature to 300°C at 5°C / min, the endothermic peak of each polymer resin is regarded as the heat of fusion, and the heat is divided by the complete crystallization heat of fusion of the polymer resin to calculate the percentage. For example, for polyvinylidene fluoride resin, the endothermic peak observed in the range of 100 to 190°C is regarded as the heat of fusion of the polyvinylidene fluoride resin, and the heat is divided by 104.6 J / g, which is the complete crystallization heat of fusion of the polyvinylidene fluoride resin, to calculate the percentage.
[0105] (v) Surface structure of the surface part (pore size, number, standard deviation)
[0106] After the porous membrane was vacuum dried at 25°C for one night, it was observed using a SEM (manufactured by Hitachi High Tech Novel Devices; S-5500) at a magnification of 30,000 to 100,000 times. The image obtained by SEM observing the surface of the porous membrane was binarized using the free software "ImageJ". When binarizing, after creating a background using SubtractBackground as 1 pixel, the condition "RenyiEntropy" was selected in Threshold (binarization threshold). In the resulting binary image, the area of each hole was determined by selecting Area in Analyze Particles, and the diameter calculated by assuming each hole to be a circle was used as the surface pore diameter. When calculating the average value of the surface pore diameter, the pore diameters of more than 1,000 holes were averaged and calculated. Similarly, the standard deviation of each surface pore diameter was calculated. The number of holes was divided by the area of the observed area to obtain the number of holes per unit area.
[0107] (vi) Self-diffusion coefficient of polymer
[0108] The self-diffusion coefficient was determined by all-atom molecular dynamics calculation. A polymer solution system was prepared in such a way that the polymer concentration (weight %) actually used was obtained. At this time, a model polymer chain was modeled in such a way that the molecular weight was 800 to 6000 and the weight average molecular weight of the polymer actually used was 1 / 200 to 1 / 5. GAFF2 was used as the potential parameter used in the molecular dynamics calculation. A pressure / temperature constant ensemble was constructed by controlling the temperature to 25°C and the pressure to 1 bar. At this time, the short-range Lennard-Johns interaction was operated by applying a switching function from 1.0nm and cutting off at 1.2nm, and the long-range electrostatic interaction was calculated by the Particle Mesh Ewald method. In the pressure / temperature constant ensemble, after the molecular dynamics calculation was performed until the density became constant, the unit cell length was adjusted in such a way that the average density was obtained, and an additional calculation of 11ns was performed in the temperature constant ensemble. Using the 10ns trajectory, the mean square displacement (MSD) of each atom of the polymer was obtained, and the self-diffusion coefficient was calculated by the following formula (3). At this time, regarding the range of MSD and t used in the calculation of D, it was confirmed that the value obtained by dividing log(MSD) by log(t) was in the range of 0.9 to 1.1. When a plurality of polymers are mixed to prepare a polymer solution, the value obtained by weighted averaging the self-diffusion coefficients of the polymers based on the weight % of the polymers is used as the self-diffusion coefficient of the polymer in the polymer solution.
[0109] D=MSD / 6t...Equation (3)
[0110] D: self-diffusion coefficient t: time.
[0111] (vii) Filtration evaluation method for chemical plant wastewater
[0112] Wastewater from a chemical plant (TOC: 30 mg / L, turbidity: 11 NTU) was supplied to a porous membrane at 25°C to give a transmembrane pressure difference of 100 kPa, and the entire amount was filtered, and the permeate volume was measured. 2 When the pressure difference between membranes was 150 kPa, reverse filtration was performed until the reverse filtration permeation rate reached 3 L / m 2 Filtration and back filtration were repeated, and the filtration flux (F1) at the beginning of filtration and the amount of permeate per unit area were calculated to be 400 L / m 2 The ratio of the filtration flux at the beginning of the filtration (F2) after the above (F2 / F1): the initial ratio of the filtration flux. The closer the initial ratio of the filtration flux is to 1, the more the initial characteristics are maintained. The porous membrane is not easily clogged even after long-term use, and the standard for good filtration is 50% or more.
[0113] (viii) Cross-sectional structure of the outermost surface (presence of nano-network structure, pore size, number, standard deviation)
[0114] The porous membrane embedded with a commercially available embedding agent for frozen tissue sectioning (made by Theisu Tech; OCT Conpad) was sliced with a thickness of 100 nm at -40°C in a direction perpendicular to the surface using a cryo-ultra-thin slicer (made by Leica; FC7), and vacuum dried at room temperature for 12 hours. The cross section of the outermost part of the porous membrane was observed with a TEM (made by JEOL; JEM-1400Plus), and the image was obtained and binarized using the free software "ImageJ". When binarizing, the condition "Minimum" was selected in Threshold (binarization threshold). In the resulting binarized image, the area of each hole was obtained by selecting Area in Analyze Particles, and the diameter calculated by assuming each hole to be a circle was used as the cross-sectional pore size.
[0115] When calculating the average value of the cross-sectional pore diameter, the pore diameters of more than 1000 holes are averaged and calculated. In addition, the number of cross-sectional pores is divided by the area of the analyzed region to obtain the number of pores per unit area. The image containing more than 1000 holes is analyzed and calculated in the same way as the pore diameter. Similarly, the standard deviation of each cross-sectional pore diameter is calculated. The total circumference of the cross-sectional pore diameter is obtained by binarizing the TEM image of the cross section of the porous membrane as described above and selecting Perim in Analyze Particles to obtain the circumference of each hole, and dividing it by the area of the region where the total is observed. In the surface portion of the porous membrane, the average value of the cross-sectional pore diameter [nm] in the cross section of the outermost portion from the surface to a thickness of 2μm is 1nm to 99nm, and the number of cross-sectional pores is 100 / μm. 2 ~1000 / μm 2 In the case of a network structure, it is judged to have a nano-network structure.
[0116] (ix) Biopolymer concentration and biopolymer removal rate
[0117] The biopolymer concentrations of the treated water and the water supplied to the reverse osmosis membrane were measured by size-exclusion chromatography with organic carbon detection (LC-OCD) as described in Huber, SA, Balz, A., Abert, M., Pronk, W., 2011. Characterization of aquatic humic and non-humic matter with size-exclusion chromatography e organic carbon detection e organic carbon detection e organic nitrogen detection (LC-OCD-OND). Water Research 45(2), 879-885. A 250 mm × 20 mm TSK HW50S column was used, the flow rate was 1.1 mL / min, the sample injection volume was 1 mL, the UV wavelength was 254 nm, the acid injection volume for OCD was 0.2 mL / min, pH 6.85 phosphate buffer was used as the eluent, and as an acidification solution, 4 mL of O-phosphoric acid (85%) and 0.5 g of potassium persulfate were added to 1 L of ultrapure water.
[0118] (x) Reduction rate of water permeability of reverse osmosis membrane
[0119] The reverse osmosis membrane was operated at a pressure of 5.5 MPa and a recovery rate of 37%. The recovery rate is calculated by the flow rate of water permeating the reverse osmosis membrane / (the flow rate of water permeating the reverse osmosis membrane + the flow rate of concentrated water in the reverse osmosis membrane) × 100. Here, the water permeability reduction rate of the reverse osmosis membrane is calculated based on the formula (4) using the flow rate of water permeating 1 hour after the start of the operation of the reverse osmosis membrane and the flow rate 50 hours after the start of the operation. Here, the permeate water volume (g) of 5 minutes is used for each flow rate.
[0120] Reverse osmosis membrane water permeability reduction rate [% / hr] = (permeated water volume [g] 51 hours after the start of operation) / (permeated water volume [g] 1 hour after the start of operation) / 50 × 100 ... formula (4).
[0121] (xi) Initial value ratio of ultrafiltration membrane permeability
[0122] The treated water was supplied to the ultrafiltration membrane in such a way that the pressure difference between the membranes became 100 kPa, and the entire amount of filtration was performed, and the amount of permeated water was measured. When the amount of permeated water became 28 L / m2, reverse filtration was performed in such a way that the pressure difference between the membranes became 150 kPa until the reverse filtration permeable water amount became 3 L / m2. Filtration and reverse filtration were repeated, and the flow rate F1 (g) of the permeated water immediately after the filtration in the ultrafiltration membrane was started, and the flow rate F2 (g) of the permeated water immediately after the filtration was started after the amount of permeated liquid per unit area became 400 L / m2 or more was measured. Here, the permeated water amount (g) for 5 minutes was used for each flow rate, and the ratio of the permeated water flow rates (F2 / F1) was calculated as the initial value ratio of water permeability.
[0123] (Example 1)
[0124] The porous membrane used was a hollow fiber porous membrane including a support obtained by the following method. 38% by mass of PVDF (manufactured by Kureha Corporation; KF1300, weight average molecular weight 350,000 Da) and 62% by mass of γ-butyrolactone were mixed and dissolved at 160°C to prepare a support membrane stock solution. The support membrane stock solution was discharged from a double nozzle die while an 85% by mass γ-butyrolactone aqueous solution was accompanied as a hollow portion forming liquid. The discharged support membrane stock solution was solidified in a cooling bath at a temperature of 20°C set 30 mm below the nozzle die and added with an 85% by mass γ-butyrolactone aqueous solution, to produce a hollow filamentous support having a spherical structure.
[0125] 12 mass% of PVDF1 (manufactured by Alchemy Co., Ltd.; Kynar (registered trademark) 710, weight average molecular weight 180,000 Da), 4.8 mass% of cellulose diacetate (manufactured by Isterman Co., Ltd.; CA-398-3), 2.4 mass% of cellulose triacetate (manufactured by Isterman Co., Ltd.; CA-436-80S), 68.7 mass% of NMP, and 12.1 mass% of 2P were mixed and stirred at 120°C for 4 hours to prepare a polymer solution having the composition ratio shown in Table 1.
[0126] Next, a polymer solution (thickness 50 μm) was uniformly applied to the outer surface of the hollow filamentous support at a speed of 10 m / min. One second after the support coated with the polymer solution was immersed in a coagulation bath of distilled water at 35°C for 10 seconds to coagulate it, thereby forming a porous membrane with a three-dimensional network structure. The evaluation results of the obtained porous membrane are shown in Table 1. The surface portion of the porous membrane from the surface to the thickness of 10 μm is denser than the inner portion. An image of a cross section of the outermost surface of the porous membrane observed by TEM is shown in Figure 5 The cross-sectional pore diameter and the number of cross-sectional pores indicate that the porous membrane has a nano-network structure. α / H β The permeability of pure water is 0.43m3 / m 2 / h / 50kPa, the dextran removal rate was 55%, which is good. In addition, the crystallinity of the surface resin was as high as 49%. Furthermore, the value X obtained by dividing the number of surface pores by the average value of the surface pore diameter was 66, the average surface pore diameter was 7.2nm, and the standard deviation was 2.5.
[0127] The long-term stability was evaluated by (vii) the factory wastewater filtration evaluation method, and the permeate volume was 400 L / m 2 The initial ratio (F2 / F1) of the filtration flux after (F2) to the filtration just started (F1) was 0.63, and the filtration flux could be maintained even after long-term use.
[0128] (Example 2)
[0129] In the film formation of Example 1, NMP in the polymer solution was changed to DMSO and the distilled water in the coagulation bath was set to 40°C. A porous film was obtained by similar film formation. The evaluation results of the porous film are shown in Table 1. The surface portion of the porous film from the surface to a thickness of 10 μm was denser than the inner portion. The H α / H β The permeability of pure water is 0.29m 3 / m 2 / h / 50kPa, the dextran removal rate was 63%, which was good.
[0130] Furthermore, X was 78, the average surface pore size was 7.3 nm, and the standard deviation was 1.8. The long-term stability was evaluated by (vii) the filtration evaluation method of factory wastewater, and the permeate volume was 400 L / m 2 The initial ratio (F2 / F1) of the filtration flux after (F2) to the filtration just started (F1) was 0.55, and the filtration flux could be maintained even after long-term use.
[0131] (Example 3)
[0132] In the film formation of Example 1, the NMP in the polymer solution was changed to DMF and the distilled water in the coagulation bath was set to 25°C. A porous film was obtained by the same film formation. The evaluation results of the porous film are shown in Table 1. The surface portion of the porous film from the surface to a thickness of 10 μm was denser than the inner portion. The H α / H β The permeability of pure water is 0.45m 3 / m 2 / h / 50kPa, the dextran removal rate was 47%, which was good.
[0133] Furthermore, X was 48, the average surface pore size was 8.5 nm, and the standard deviation was 3.1. The long-term stability was evaluated by (vii) the filtration evaluation method of factory wastewater, and the permeate volume was 400 L / m 2 The initial ratio (F2 / F1) of the filtration flux after (F2) to the filtration just started (F1) was 0.50, and the filtration flux could be maintained even after long-term use.
[0134] (Comparative Example 1)
[0135] In the film formation of Example 1, the solvent in the polymer solution was all NMP, and the composition ratio was changed. The film formation was similar to obtain a porous film. The evaluation results of the porous film are shown in Table 2. The porous film does not have a nano-network structure. The surface portion of the porous film from the surface to a thickness of 10 μm is denser than the interior. The H α / H β is 1.0, and the permeability of pure water is 0.41m 3 / m 2 / h / 50kPa, the dextran removal rate was 55%. Furthermore, X was 13, the average surface pore size was 15nm, and the standard deviation was 6.0. In addition, the crystallinity of the surface resin was as low as 11%. The long-term stability was evaluated by the filtration evaluation method of factory wastewater (vii), and the result was that the permeate volume was 400L / m 2 The initial ratio (F2 / F1) of the filtration flux after (F2) to the filtration just started (F1) was 0.38, and the filtration flux could not be maintained after long-term use.
[0136] (Comparative Example 2)
[0137] A porous membrane was obtained by similarly forming the membrane in Comparative Example 1 except that the coagulation bath temperature was 6°C. The evaluation results of the porous membrane are shown in Table 2. The surface portion of the porous membrane from the surface to a thickness of 10 μm was denser than the inner portion. The H α / H β is 0.10, and the permeability of pure water is 0.10m 3 / m 2 / h / 50kPa, the glucan removal rate was 70%, which did not meet the conditions. Furthermore, X was 10, the average surface pore size was 8.0nm, and the standard deviation was 1.9. The long-term stability was evaluated by (vii) the factory wastewater filtration evaluation method, and the result was that the permeate volume was 400L / m 2 The initial ratio (F2 / F1) of the filtration flux after (F2) to the filtration just started (F1) was 0.37, and the filtration flux could not be maintained after long-term use.
[0138] (Comparative Example 3)
[0139] In the film formation of Example 1, PVDF1 in the polymer solution was replaced with PVDF2 (Solef9009, manufactured by Solbey Co., Ltd.) and the composition ratio was changed. A porous film was obtained by film formation in the same manner as in Comparative Example 1. The evaluation results of the porous film are shown in Table 2. The porous film does not have a nano-network structure. The surface portion of the porous film from the surface to a thickness of 10 μm is denser than the interior. The H of the obtained porous film α / H β The permeability of pure water is 0.21m 3 / m 2 / h / 50kPa, the glucan removal rate was 57%. Furthermore, X was 7.6, the average surface pore size was 10nm, and the standard deviation was 4.1, which did not meet the conditions. The long-term stability was evaluated by (vii) the factory wastewater filtration evaluation method, and the result was that the permeate volume was 400L / m 2 The initial ratio (F2 / F1) of the filtration flux after (F2) to the filtration just started (F1) was 0.40, and the filtration flux could not be maintained after long-term use.
[0140] (Comparative Example 4)
[0141] 20% by mass of PVDF3 (manufactured by Kleha Corporation; KF Polymer #110, weight average molecular weight 280,000 Da) and 80% by mass of a mixed solvent (DMAc:GBL=89:11) were mixed and stirred at 120°C for 4 hours to prepare a polymer solution. In addition, the distilled water in the coagulation bath was set at 21°C, and a porous membrane was obtained by forming a membrane in the same manner as in Example 1. The evaluation results of the porous membrane are shown in Table 2. The H of the obtained porous membrane α / H β The permeability of pure water is 0.022m 3 / m 2 / h / 50kPa, the glucan removal rate was 66%, which did not meet the conditions. Furthermore, X was 0.90, the average surface pore size was 15nm, and the standard deviation was 8.5. The long-term stability was evaluated by the filtration evaluation method (vii) of factory wastewater, and the result showed that the amount of permeate was significantly small, making it difficult to measure the filtration flux.
[0142] (Example 4)
[0143] use Figure 6The process shown in the figure produces permeate water of the reverse osmosis membrane from the water to be treated. That is, seawater 1 (biopolymer concentration 122μgC / L) is used as the water to be treated, and the porous membrane of Example 1 is used for pretreatment. As a result, the biopolymer concentration of the water provided to the reverse osmosis membrane is 35μgC / L. The permeate water is obtained by pressurizing the water to be provided to the reverse osmosis membrane with a high-pressure pump and filtering it with a reverse osmosis membrane. The reverse osmosis membrane is made of polyamide, has a desalination rate of 99.8%, and a membrane area of 37m 2 Spiral reverse osmosis membrane.
[0144] Here, the water permeability initial value ratio of the ultrafiltration membrane was 0.71, and the water permeability reduction rate of the reverse osmosis membrane was 0.15% / hr. Although the biopolymer concentration in the treated water was high, the filtration of the ultrafiltration membrane was stable without using a flocculant, and the filtration of the reverse osmosis membrane was also stable. The results are shown in Table 3.
[0145] (Example 5)
[0146] use Figure 6 The process shown in the figure produces permeate water of the reverse osmosis membrane from the water to be treated. That is, seawater 2 (biopolymer concentration 218μgC / L) is used as the water to be treated, and the porous membrane of Example 1 is used for pretreatment. As a result, the biopolymer concentration of the water provided to the reverse osmosis membrane is 47μgC / L. The permeate water is obtained by pressurizing the water to be provided to the reverse osmosis membrane with a high-pressure pump and filtering it with a reverse osmosis membrane. The reverse osmosis membrane is made of polyamide, has a desalination rate of 99.8%, and a membrane area of 37m 2 Spiral reverse osmosis membrane.
[0147] Here, the water permeability initial value ratio of the ultrafiltration membrane was 0.63, and the water permeability reduction rate of the reverse osmosis membrane was 0.18% / hr. Although the biopolymer concentration in the treated water was very high, the filtration of the ultrafiltration membrane was stable without using a flocculant, and the filtration of the reverse osmosis membrane was also stable. The results are shown in Table 3.
[0148] (Comparative Example 5)
[0149] use Figure 6 The process shown in the figure produces permeate water of the reverse osmosis membrane from the treated water. That is, seawater 1 (biopolymer concentration 122μgC / L) is used as the treated water, and the porous membrane of Comparative Example 1 is used for pretreatment. As a result, the biopolymer concentration of the water provided to the reverse osmosis membrane is 85μgC / L. The permeate water is obtained by pressurizing the water provided to the reverse osmosis membrane with a high-pressure pump and filtering it with a reverse osmosis membrane. The reverse osmosis membrane is made of polyamide, has a desalination rate of 99.8%, and a membrane area of 37m 2 Spiral reverse osmosis membrane.
[0150] Here, the water permeability initial value ratio of the ultrafiltration membrane was 0.53, and the water permeability reduction rate of the reverse osmosis membrane was 0.25% / hr, indicating that the permeability reduction rate of the reverse osmosis membrane was large.
[0151] (Comparative Example 6)
[0152] use Figure 6 The process shown in the figure produces permeate water of the reverse osmosis membrane from the treated water. That is, seawater 2 (biopolymer concentration 218μgC / L) is used as the treated water, and the porous membrane of Comparative Example 1 is used for pretreatment. As a result, the biopolymer concentration of the water provided to the reverse osmosis membrane is 139μgC / L. The permeate water is obtained by pressurizing the water provided to the reverse osmosis membrane with a high-pressure pump and filtering it with a reverse osmosis membrane. The reverse osmosis membrane is made of polyamide, has a desalination rate of 99.8%, and a membrane area of 37m 2 Spiral reverse osmosis membrane.
[0153] Here, the water permeability initial value ratio of the ultrafiltration membrane is 0.45, and the water permeability reduction rate of the reverse osmosis membrane is 0.45% / hr. Perhaps because the biopolymer concentration in the treated water is very high, the water permeability of the ultrafiltration membrane is greatly reduced, and the permeability reduction rate of the reverse osmosis membrane is significantly large. The results are shown in Table 3.
[0154]
[0155]
[0156]
[0157] Explanation of symbols
[0158] 101 porous membrane
[0159] 102 Surface
[0160] 103 Interior
[0161] 201 Coarse Pollution Components
[0162] 202 Microscopic Pollution Components
[0163] 300 polymer solution
[0164] 301 Phase containing a large number of polymers
[0165] 302 Phase containing a large amount of solvent
[0166] FL filter direction
[0167] 401 Treated water
[0168] 402 Reverse Osmosis Membrane
[0169] 403 Through Water
[0170] 404 Concentrated water
[0171] 405 Pre-treatment process
[0172] 406 is used to provide water to the reverse osmosis membrane
[0173] 407 High Pressure Pump
[0174] 408 Transfer Pump
[0175] 409 Supply Pump
[0176] 410 Detergent
[0177] 411 Fungicide.
Claims
1. A porous membrane comprising a polyvinylidene fluoride resin, wherein one surface is defined as a surface A and the other surface is defined as a surface B, and the α-type structure crystal H in the crystalline part of the polyvinylidene fluoride resin measured by the ATR method on the surface A is α With β-type structure crystal H β The ratio of H α / H β The ratio is greater than 0 and less than 0.50, The pure water permeability of the porous membrane is 0.25 m 3 / m 2 / h / 50kPa or above and 1.2m 3 / m 2 / h / 50 kPa or less, and an average value of the surface pore diameters of the surface pores in the surface A of the porous membrane is 5.0 to 12.0 nm. 2 . The porous membrane according to claim 1 , wherein the polyvinylidene fluoride resin in the surface A of the porous membrane has a crystallinity of 30% or more. 3 . The porous membrane according to claim 1 , wherein the removal rate of 40,000 Da dextran of the porous membrane is 45% to 80%. 4 . The porous membrane according to claim 1 , wherein a value X obtained by dividing the number of the surface pores in the surface A of the porous membrane by the average value of the surface pore diameter is 30 pores / μm 2 / nm or more and 100 / μm 2 / nm or less, the unit of the number of surface pores is pieces / μm 2 , the unit of the average surface pore size is nm. 5 . The porous membrane according to claim 1 , wherein a standard deviation of the surface pore diameters in the surface A of the porous membrane is 1.0 nm or more and 5.0 nm or less. 6 . The porous membrane according to claim 1 , wherein a surface portion of the porous membrane from the surface A to a thickness of 10 μm is denser than an inner portion.
7. A method for filtering a liquid, wherein: The porous membrane according to any one of claims 1 to 6 is used. 8 . A membrane filtration device comprising the porous membrane according to claim 1 .
9. A method for producing water, comprising a pretreatment step and a reverse osmosis membrane treatment step, wherein the pretreatment step pre-treats the water to be treated to obtain water to be supplied to a reverse osmosis membrane, and the reverse osmosis membrane treatment step filters the water to be supplied to the reverse osmosis membrane using a reverse osmosis membrane to obtain permeated water, In the water production method, the water to be treated is water to be treated having a biopolymer concentration of 100 μgC / L or more, the water to be supplied to the reverse osmosis membrane having a biopolymer concentration of 75 μgC / L or less is obtained through the pretreatment step, and the water is supplied to the reverse osmosis membrane treatment step. The pre-treatment step includes an ultrafiltration membrane treatment unit having an ultrafiltration membrane, The ultrafiltration membrane is the porous membrane according to any one of claims 1 to 6.
10. The method for producing fresh water according to claim 9, wherein the number of surface pores in the surface A of the porous membrane is 200 pores / μm 2 Above and 2000 / μm 2 the following.
11. The method for producing fresh water according to claim 9 or 10, characterized in that: In the ultrafiltration membrane treatment in the pretreatment step, the water to be treated does not contain a flocculant.
Citation Information
Patent Citations
A sauger attachment
CA43680S
Porous hollow fiber membrane, and manufacturing method of the same
JP2015073916A
Hollow fiber membrane and method of producing hollow fiber membrane
JP2017029934A
Resin composition manufacturing method, porous film manufacturing method, and porous film
JP2021176629A